Oil Accumulation and First Fire Readiness Analysis of Cylinder Deactivation - Halbe, Mayura; Pietrzak, Brad; Fain, David; Ramesh, Aswin; Shaver, Greg; McCarthy, James E.; Ruth, Mike; Koeberlein, Edward (Frontiers in Mechanical Engineering, 2017)
Cylinder deactivation (CDA) is a technology that can improve the fuel economy and exhaust thermal management of compression ignition engines (diesel and natural gas), especially at low loads and engine idling conditions. The reduction in engine displacement during CDA improves fuel efficiency at low loads primarily through a reduction in pumping work. During deactivation of a given cylinder, the drop in pressure inside the cylinder could possibly lead to the transport of oil from the crankcase into the cylinder owing to the reduced pressure difference between the crankcase and the cylinder. In addition, CDA might inhibit the first fire readiness of a reactivating cylinder as a result of reduced wall, head, and piston temperatures. Both of these potential issues are quantitatively studied in this article. This article describes a strategy to estimate in-cylinder oil accumulation during CDA, and first fire readiness following CDA, through comparison of individual heat release profiles before and after CDA. Cylinder cool-down and oil accumulation during deactivation could possibly result in misfire or degraded combustion upon an attempt to reactivate a given cylinder. Fortunately, experiments described in this article demonstrate no cases of misfire at any speed/load conditions for the CDA durations tested, specifically 100 ft-lb load at 800 rpm and 1,200 rpm with deactivation intervals of 0.5, 5, 10, and 20 min. Although pilot heat release in the reactivated cylinders was delayed by approximately 1 CAD after 5 min of CDA, the main heat release was very similar to the heat release of a continuously activated cylinder. As such, results show no first fire readiness issues at the conditions tested. The duration of time the engine could be operated in CDA mode without significant oil accumulation and other methods to minimize oil accumulation during CDA have also been proposed.